POLITICAL DISCOURSE ON SERBIA IN THE MEDIA REPORTING OF THE SELECTED WESTERN COUNTRIES - Novković, Nenad (National interest, 2025)
The paper presents the results of research on the discourse on Serbia in selected Western media since the beginning of the military operation in Ukraine. The conducted research included the analysis of the original content of articles published on the Bild, BBC, and The New York Times websites, showing that the current discourse on Serbia was mostly established in the 1990s, during the Balkan conflicts, when the previous, positive image of the country as part of the SFR Yugoslavia was replaced by a negative one, awakening earlier references to the entire Balkan region. Historically, the West has viewed the Balkans as a collection of barbarians who, although in Europe, are distant from the European civilization, concluding that only distancing from their own past and identity and acceptance of European norms can help the Balkan countries break away from the tribal and backward. The process of portraying Serbia through the notions of Balkanism and Nazification later grew into the overall demonization of the country and its people. Serbia has been labelled as the main and only culprit for the Balkan conflicts, the discourse promoted by the Western politicians and broadcast by the media and eventually accepted by the public, about a backward and genocidal country that deserves to be destroyed. Legitimacy to this narrative has been given by institutions such as the ICTY, which changed the interpretation of genocide to make it applicable to the Serbian case, and various Western intelligence organisations that fabricated evidence in order to get the public support for the intervention against Serbia. In the midst of the negative campaign, various marketing agencies were used to promote the desired discourse, creating false information about the existence of concentration camps and a narrative similar to the one that existed against Nazi Germany in order to minimize resistance to the punitive measures that the West intended for Serbia. Western media selected for the purposes of this paper primarily choose sensationalist topics related to the field of politics and crime in the relevant period, mostly reporting on the relationship between Serbia and Kosovo, the influence of Russia on Serbia and the Balkans, the elections and the Serbian president, protests, and mass shooting in Belgrade. Portal bild.de mentioned Serbia in 24 articles in an almost exclusively negative connotation. bbc.com rarely reported on Serbia in the given period, mentioning it only 14 times with a little more journalistic objectivism keeping neutrality in about 43% of the articles. nytimes.com is a true example of journalism of attachment because it uses every opportunity to report on Serbia in a negative manner. By creating such an image in 35 articles, out of which 86% presented Serbia in a negative connotation, The New York Times continues the negative campaign against the country from the 1990s in order to support the official goals of the West such as the recognition of Kosovo and the acceptance of full responsibility for the Balkan conflicts, including genocide. Serbia is, therefore, depicted as an autocratic, nationalistic, stubborn country, featuring no freedom of the press, still living in the legacy of the wartime past, such as a high degree of armament of the population, non-reconciliation with the past and non-acceptance of international positions regarding Kosovo’s independence or blame for ethnic cleansing in the Balkans. The country is also connected to organized crime, hooligan groups with roots in paramilitary groups, and a right-wing president who is holding the country in the grip of nationalism and his far-right past.